3d+(9-2d)=51

Simple and best practice solution for 3d+(9-2d)=51 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3d+(9-2d)=51 equation:


Simplifying
3d + (9 + -2d) = 51

Remove parenthesis around (9 + -2d)
3d + 9 + -2d = 51

Reorder the terms:
9 + 3d + -2d = 51

Combine like terms: 3d + -2d = 1d
9 + 1d = 51

Solving
9 + 1d = 51

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 1d = 51 + -9

Combine like terms: 9 + -9 = 0
0 + 1d = 51 + -9
1d = 51 + -9

Combine like terms: 51 + -9 = 42
1d = 42

Divide each side by '1'.
d = 42

Simplifying
d = 42

See similar equations:

| 4t+1/4=t+5/8+t-3/8 | | 4x+18=180 | | 9x^2-12=13 | | 6+2j-4=4 | | -n-(3+9n)=-10-14n | | t+.02t=612 | | 4a+0.2=50 | | 2.9y-4.6=0.6y | | 7z-6z=18+4 | | 2x-3(4x+5)-10=10x+3-4 | | (x-3)(x+3)=2x^2+3x+29 | | 23/6x5/6+23/6x13/6 | | -1/3+2t=-1/3(9t-2) | | D=tres | | y^2-100=4y | | 10y-4y-8=20 | | (u-4)^2/3 | | 4k=60+6k | | 9/5(k-273.15) | | 3-2/6b=1/3b-7 | | k+10/k=4/6 | | 10(x^2-21x+75)=0 | | 5x+2(5x-2)=176 | | 3(2x-2)=4(x+4) | | 8x+10-2x+36=4x+15+8x-28 | | n+1=13-2n+n | | 10y-4-8=20 | | 3(3.99)+1b-0.11=5b | | (2x-3)(2x+3)=55 | | x^2-21x+75=0 | | 5y-4=8+y | | 3x-2=7x+6 |

Equations solver categories